Study of clinicodemographic profile of acute central nervous system infection in children and its correlation with neuroimaging - Vasavada, Halak J.; Patel, Snehal V.; Detroja, Kuldip A.; Patel, Aakanksha R.; Patel, Mitsu N. (International Journal of Contemporary Pediatrics, 2022)
Background: Infection of central nervous system (CNS) is most common cause of fever associated with signs and symptoms of CNS disease in children. Viral infections of CNS are more common than other infections. Radiology and pathology go together in understanding etiology causing CNS infections which have similar clinical manifestations making specific diagnosis difficult. The present study aims to study the utility of different neuroimaging patterns in diagnosis of acute CNS infection. Aims include: to study utility and pattern of neuroimaging in CNS infection in paediatric age group, and to study socio-demographic and clinical profile of CNS infection in children. Methods: Prospective observational study in children 1 month-12 years who presented with CNS infection. Results: Total 58 cases were suspected to have CNS infection, which was more prevalent in 1 month-1 year (27.58%), followed by 5-8 year (24.13%), 1-3 year (22.41), >8 year (20.68%) and 3-5 year (5.17%). Neuroimaging was done in all suspected case (58) of CNS infection in which 30 (51.7%) had abnormal neuroimaging where 3(10%) showed pyogenic meningitis, 7 (23.23%) tubercular meningitis (TBM), 4 (13.13%) tuberculoma, 3 (10%) TBM and tuberculoma, 4 (13.3%) viral meningitis, 1 (3.3%) herpes simplex encephalitis (HSE), 1 (3.3%) COVID encephalitis, 4 (13.3%) acute disseminated encephalomyelitis (ADEM) while 2 (6.66%) brain abscess. Correlation between final diagnosis and neuroimaging was 100% in ADEM, brain abscess, tuberculoma, TB spine, HSV followed by TBM (77.77%), pyogenic meningitis (27.27%) and viral encephalitis (26.66%). Clinically diagnosed acute CNS infection was confirmed in 51.72% and wrong in 48.27%. Conclusions: CNS infections were more common in less than 5 years age. Approximately 50% patients had abnormal neuroimaging finding. It was found that neuroimaging was more accurate in early diagnosis, categorization of CNS infection and detection of complications with high sensitivity.